(untitled) (Comprehensive Journal of Science, 2026)
This research examines the implications of the Iranian–Israeli conflict on Arab national security, recognizing this confrontation as one of the key determinants of regional stability in the Middle East. The study analyzes the direct and indirect threats posed by the conflict, including military escalation, cyberattacks, and shifts in regional alliances. It also explores potential future scenarios and their impact on Arab national security. The research concludes with a set of findings and recommendations aimed at enhancing the resilience of Arab states in addressing emerging security challenges.